ANALISA PENGARUH PARTIKEL SiC TERHADAP SIFAT MEKANIS METAL MATRIX COMPOSITE DIBUAT MENGGUNAKAN METODE CENTRIFUGAL CASTING - Harahap, Fadel Muhammad; Tugiman, Tugiman; Suprianto, Suprianto (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2015)
Metal matrix composites have properties that are resistant to corrosion and wear compared to metal without reinforcement. Increased use of composites is due to have a low density and relatively low-cost amplifier. Aluminum matrix composites have strength, specific modulus and good wear resistance compared to aluminum alloys without reinforcement. The purpose of this study to better understand the mechanical properties and microstructure of Al-SiC with experimental testing. Composite Silicon carbide (SiC) is prepared with the weight fraction of 1.5%, 2.5% and 3.5%. Casting method used is Centrifugal Casting by pouring temperature 735 ° C, stirring for 2 minutes long and 381 rpm rotation. The test results obtained on the composition of Al-SiC most excellent on mechanical properties and microstructure are SiC content of 3.5%. The maximum value of 62.03 BHN hardness and a minimum value of 48.42 BHN hardness, impact a maximum of 45.42 joules and a minimum of 31.08 joule impact with maximum impact value of 0. joule/〖mm〗^2 and the minimum impact value of 0.310 joule/〖mm〗^2, resistance SiC wear rate of 3.5% in theory at 0,311 〖mm〗^3/S, experimentally by 0.320 〖mm〗^3/S and the rate of wear and tear on the theoretical Raw material of 0.401 〖mm〗^3/S, as experiments 0.415 〖mm〗^3/S. It can be concluded that the content of Al-SiC 3.5% have hardness, impact and wear resistance is higher than the Raw material. This is in accordance with the micro-structure photograph SiC content more widely available on the variation of 3.5% compared with the variation Raw material composition.